Hakikat Keilmuan Ilmu Hukum - Marcel Seran (Universitas Atma jaya Makassar, 2011)
The nature of the science of law is often questioned. The question is with regard whether or not the law belongs to a science. If it belongs to a science, then what science is it categorized? Does it belong to social, natural or human science? A debate on this is certainly interesting, because some argue that the law is a natural science. ...........................